Pengaruh Musim Terhadap Distribusi Temperatur, Salinitas Dan Densitas Di Laut Halmahera - Delilla Suhanda; Muhammad Gilang Arindra Putra (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2021)
The Halmahera Sea is one of the waters that has an important role for the development of Indonesia's climate. The waters of the Halmahera Sea are the ARLINDO route which is part of the global circulation flow. This study aimed to examine the horizontal and vertical temperature profiles, salinity density and T-S diagrams in the Halmahera Sea. The results showed that the horizontal and vertical profiles in the two seasons did not have a significant effect, this could be due to the movement of the New Guinea air mass along the coast of North Papua, then into the Halmahera Sea. T-chart showed the current moving in the Halmahera Sea vertically, including the SPSW or South Pacific Subtropical Water category, as evidenced by a salinity value of 34.7 PSU and a temperature value of 14oC at a depth of 500 m.